Qualitative research in the accounting field: insights towards the grounded theory approach - Martins, Adelaide (2020)
The choice of the research methodology is a critical stage of any research project. The complexity of the business environment and the multifaced nature of many accounting practices have resulted in an increased use of qualitative research methodology. Grounded theory is particularly appropriate when studying accounting in its social context. However, an abductive approach is helpful to study how qualitative studies are actually performed. Both grounded theory and an abductive approach offer enormous potential for application in the development of accounting theories from qualitative case studies. Despite its popularity as a research methodology in other social sciences, grounded theory remains scarcely explored by accounting researchers. Mixed methods have been gaining increasing attention in the qualitative accounting literature, but with some levels of resistance. There is significant potential for mixed methods in accounting research for both theory testing and theory building. The aim of this paper is to provide an informative reference work on qualitative research methodology. In particular, this paper offers an insight into some issues and debates which are emerging from grounded theory approach and the abductive mode of reasoning, as well as mixed methods application and their potential within the context of the accounting field. Since the methodological exposition represents the major source of authenticity and credibility in a qualitative paper, this theoretical debate is particularly useful for students and emerging scholars in accounting and management disciplines.